The Realization of Refusal Strategies by Parents and Children in The Family Domain (A Case Study) - Anisah Septiany (Universitas Pendidikan Indonesia (UPI), 2013)
This study was aimed to discover the realization of refusal strategies by parents and children when refusing requests in a family domain. This study engaged a family including a father, a mother, and two children as the subject of the study. Observation was conducted by recording and noting some conversations in order to collect the data. The collected data were analyzed by applying a theory proposedby Aziz (2000). The theory was used to analyze the types of refusal strategies. The findings reveal that there are ten out of eleven strategies proposed by Aziz found in the family domain. Parents tend to use giving reason or explanation, showing hesitation and offering alternative strategy in their refusal statements whereas children mostly apply showing hesitation, giving reason or explanation, and postponements strategy. The result shows that power asymmetry in speaker-hearer relationship between parents-children and the hearers influence the selection of refusal strategies. The strategy of giving an explanation and reason is used by both parents and children frequently when refusing powerful hearers’ requests while hesitation strategy is applied when refusing the requests from equal power hearers. It is discovered that in terms of the nature of request, both parents and children have similar tendency to use giving reason and explanation strategy when refusing high imposition nature of request. Keywords: Refusal, Refusal Strategies, Requests, Speaker-Hearer Relationship, Nature of Request